PROBLEMATIKA DALAM PERJANJIAN ELEKTRONIK YANG TIDAK DILAKSANAKANNYA DENGAN ITIKAD BAIK DAN CARA PEMBUKTIANNYA - Herunata Sanjaya (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACTWe realize technology has brought society to the use of electronic systems in the activity that has greatly affected all aspects of social, cultural and legal, where there are no boundaries - geographic boundaries and quickly accepted by the public so as to enhance human progress and civilization. Electronic contract is a form of initiative and the parties in making the engagement through electronic systems (the Internet). Neither the Civil Code and the Law No.11 of 2008 has been providing a clear basis for the validity of electronic contracts.In the implementation of the electronic contract by both parties is superbly agreed, then implementing an electronic contract is done in the form of payment (payment) made by the debtor that can be done either directly or indirectly, for example through the internet facility or E-Banking, yet remain based on the national financial system, which refers to the local financial system. In the implementation of an electronic agreement may occur a default committed by one of the parties, resulting in the manufacture of electronics required point settlement agreement if the event of default. The principle of good faith in the agreement laid the groundwork for the electronics embedded in the hearts of minds of the parties in the implementation of the electronic agreement so as not to harm or be harmed either party.With the Electronic Systems has given rise to one of the new things that the existence of a new form of evidence and legally, namely electronic information, electronic documents or printouts of Electronic Information and Electronic Documents (Article 5 paragraph (1) of the Act No.11 of 2008).